The Concept of Mahdī in Shī'ī Theology - Nurul Fajri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 1999)
The Shī’ī eschatological doctrine encompasses the belief in the Imām Mahdī, or the Hidden Imām, who will reemerge at the end of time as a savior. This savior is anticipated to establish socio-political justice and equity, leading to a peaceful life grounded in Islamic teachings. In essence, the Imām Mahdī is believed to bring about an ideal religious society.